Integrating STEM Approaches into Interactive Digital Modules for Supporting Higher-Order Thinking Skills in Science Education: A Systematic Literature Review - Rahmawati, Rahmawati; Fiskawarni, Tri Hastiti; Andriani, Andi Arie; Widiasih, Widiasih (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The integration of Science, Technology, Engineering, and Mathematics (STEM) approaches into interactive digital modules (IDMs) has gained prominence as a strategy for supporting Higher-Order Thinking Skills (HOTS) in science education. This PRISMA-based systematic literature review synthesizes empirical studies published between 2022 and 2026 to examine how STEM-embedded digital modules are designed, implemented, and evaluated in relation to HOTS outcomes. Using PRISMA procedures and structured Boolean searches across major databases, 22 studies were selected and analyzed across four themes: STEM integration models, interactive design mechanisms, empirical effectiveness, and implementation challenges including scalability and equity. The findings show that modules grounded in the Engineering Design Process (EDP), inquiry-based learning, and adaptive feedback were most frequently associated with short-term improvements in analytical reasoning, problem-solving, and evaluative thinking. Quantitative evidence indicates that one AI-assisted module reported an 18.4% improvement in applied reasoning; however, differences in instruments and study designs limit direct comparison across HOTS measures. Some studies also reported short-term retention effects. The review proposes an integrative framework linking depth of STEM integration, interactive mechanisms, contextual moderators, and HOTS outcomes, and highlights inclusive design, continuous feedback, collaboration, and teacher training as key principles for sustainable, equitable, and evidence-informed implementation.